The Status and Future Prospects of Hydropower for Sustainable Water and Energy Development in Tanzania - Kichonge, Baraka (Journal of Renewable Energy, 2018)
Tanzania is among the countries with the fastest growing economy in Africa and therefore the need for affordable, clean, and most importantly sustainable electrical energy to meet her ever growing demands is pressing. In recent years, the country’s electricity needs have been largely dominated by thermal generations despite the fact that Tanzania is gifted with huge hydropower resource potential approximated at 38,000 MW with only a very small portion exploited to date. However, the exploited potential is expected to grow by commissioning of identified large and medium-scale hydropower projects with a total installed capacity of 4,765 MW currently under various stages of implementation. Moreover, the geographical location of Tanzania has several benefits to support development of small hydropower projects essential for appropriate utilization of available water resources as a way of mitigating climate challenges effects. Over the last decade, the country electricity demand along with end-use of energy has witnessed significant increases as economic development spreads towards achieving Vision 2025 goals. Proposed hydropower developments are projected to have enormous benefits in the acceleration of economic growth while contributing to greenhouse gas emissions reduction. In this paper, hydropower, which is one of the domestic options for clean energy development path, its present and future potential status, and water resources are explored based on a comprehensive review of energy sector relevant documents and polices.